PERBANDINGAN KELUARAN PANEL SURYA DENGAN DAN TANPA SISTEM PENJEJAK - reni listiana; Tri Handayani Yasmin (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Solar power plants are power plants that convert solar energy (light) into electrical energy. Generation of electricity can be done by using photovoltaic or can also called solar cell, which happened at this time, solar cell can not absorb sunlight optimally, because solar cell only silent in one direction (static) therefore needed smart system for generator Solar power for solar power plants to work more optimally, to make the smart system is needed to read data from several sensors. To find the direction of the arrival of the sunlight rays, used four light dependent resistor sensor (LDR). Light intensity data processing, motor rotation direction determination and other sensor data will be done by microcontroller. Then the data residing on the solar power plant will be displayed on the display and measured how much different in voltage, current and power generated by solar panel. Then the output of the solar power plant be compared among the system with tracking and without tracking.